Empowering Leadership Questionnaire: A Validation Study - Bob Foster (STMIK Mardira Indonesia, Bandung, 2019)
This study aims to validate the instrument empowering leadership questionnaire (Arnold, Arad, Rhodes & Drasgow, 2000). This instrument develops concerning the effectiveness of the leader in the team members. The factorial analysis was conducted to prove whether this instrument is relevant to Indonesia's retail sector's existing conditions. Psychometric analysis resulting from calculations using a sample of 206 employees at retail companies in Bandung shows that some instruments are invalid. However, in general, this instrument can be adapted to measure leaders' effectiveness in empowering employees. Keywords: leadership, empowerment, team member.